Kajian Faktor-Faktor Penyebab Tidak Berfungsinya Pasar Rakyat di Bone Bolango Pasca Pembangunan - Alexander Badjuka; Putri Salsabila Naleko; Syalwa Reyhana Pasilia; Rinjani Hurratun Idrisah H; Moh. Tegar Pratama Bito; Syahrul Salif N. ismail (Studi Administrasi Publik dan ilmu Komunikasi, 2026)
Traditional markets are one of the public economic facilities developed by the government to support trading activities and improve community welfare. However, not all traditional markets that have been built can function optimally. This study aims to examine the factors causing the dysfunction of traditional markets in Bone Bolango after construction. This research used a qualitative approach with a descriptive method. Data collection techniques were carried out through observation, interviews, and documentation. The informants consisted of local communities, traders, and individuals who understood the condition of the traditional market. The results showed that the dysfunction of the traditional market in Bone Bolango was influenced by several factors, including the impact of the Covid-19 pandemic which reduced community economic activities, the less strategic market location, low public interest in shopping at the market, and the large number of traders leaving the market due to the lack of consumers. In addition, the lack of sustainable economic activities around the market also caused the market to develop poorly. This study indicates that the success of traditional market development is not only determined by physical construction but is also influenced by location factors, community socio-economic conditions, and market management. Therefore, the government needs to pay attention to community needs and market management strategies so that traditional markets can function optimally.